Britain and terrorism: a sociological investigation - Dunning, Michael (Palgrave studies on Norbert Elias, 2021)
Introduction: Research on Terrorism as Part of the Terrorism Problem.-Section 1: The Sociogenesis of Terrorism in Nineteenth Century Britain -- Chapter 1: The Development of the Concept of Terrorism in Antithesis to the Concept of Civilisation -- Chapter 2: The Sociogenesis of Terrorism in Nineteenth Century Britain in Relation to Ireland -- Chapter 3: Trades Unions, Political Reformers, Revolutionary Europe and Terrorism -- Section 2: The Sociogenesis of Terrorism in Twentieth and Twenty-First Century Britain -- Chapter 4: The World Wars and the Cold War – Terrorism and Inter-State Violence -- Chapter 5: The Sociogenesis of Terrorism, the End of the British Empire, the Middle East and International Terrorism -- Chapter 6: The Fault-Lines in the British Monopoly of Violence and ‘Domestic’ Terrorism -- Section 3: Micro-Level Processes and Jihadist Terrorism in Britain. -- Chapter 7: Case Study: the 7/7 Bombers. -- Chapter 8: Case Study: British Jihadis in Syria and Iraq -- Conclusion.